Cultural heritage as the basis for the harmonious development of a personality in the modern information society - I. A. Dorofeeva (Вестник Майкопского государственного технологического университета)
The article reveals some features of statehood formation in the Republic of Belarus and the role of culture in this process. We are talking about the difficult historical conditions in which the formation of the state took place, the accumulation of material cultural heritage, spiritual values, folk traditions, customs and rituals. Modern problems of pressure on young people from Western liberal ideology pose a threat to the formation of civil identity in the Republic of Belarus. Updating the role of the traditional cultural heritage of the Belarusian people is becoming an important factor in countering this. The goal of the research is to reveal the features of socio-cultural construction in the Republic at the present stage. The method of socio-historical analysis is used. The special role of the Soviet period of social development has been highlighted, when the cultural life of the country received a new breath. It has also been noted that in the first half of the 21st century, the formation of the Union State, the economic growth and cultural development of the country played a huge role in the formation of a rich material and spiritual heritage, and the education of civic and patriotic personality traits in young people. Material is presented on improving the status of cultural institutions in the republic. As a result, it has been concluded that an important factor in the growth of authority and recognition of the Republic of Belarus in the international arena was its peace-loving policy and stabilization of public life, the adoption of the Constitution, state symbols «anthem, coat of arms and flag», decisions of the People’s Assembly, Presidential decrees and government regulations.